(untitled) (Czech Journal of International Relations, 2024)
Kai-Olaf Lang: born in 1967, student at the University of Konstanz (Faculty of Administrative Sciences), completed his internship at the Institute Political Sciences, University of Warsaw ( 1993/1994). His main research interests are in the field of political development in Poland.